Correctional protege mentorship as an effort of resocialization in class II special correctional institution for children of Kendari - Arifai Arifai; Zainuddin Zainuddin (Faculty of Law, University of Muhammadiyah Malang, 2021)
Mentorship for correctional proteges is basically an effort to re-socialize proteges when they return to society. The research constructs how the implementation of the correctional protege mentorship system so that correctional protege can be well received by the community. This research is empirical and is descriptive. The research finding shows that the mentoring carried out by LPKA Class II Kendari is personality mentorship which includes religious mentoring in the form of congregational prayer guidance, religious lecture (kultum), and reading and writing of the Koran. Mentoring legal awareness in the form of legal education. Skills mentorship in the form of making hydroponics, making chairs from aqua bottles and trash, and making handicrafts such as ashtrays and bracelets. The implementation of mentorship at LPKA Class II of Kendari has not been optimally carried out. This will have an adverse impact on correctional protege when they reintegrate with communities that are still giving them a negative stigma.